دور الصادرات الخدمية في الناتج المحلي الإجمالي في سورية دراسة قياسية للفترة ((2011-1990 - قنوع, نزار; العشعوش, أيمن; كنيفاتي, ربا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The tertiary sector is one of the most important indicators of the economic transformation and it comes after the secondary sector, as well as its important contribution to economic growth especially in developing countries. Therefore, the main aim of this research is to find out the effect of service exports in Syria's GDP, as the research starts by studying Syria's exports of goods and services, and the structure of service exports, then examining the relation between service exports and total exports as well as the relation between service exports and GDP. The research recapitulates that there is a positive effect of service exports on total exports and a positive effect also of service exports on GDP in Syria. That's the result that shows the importance of service exports and especially in future. يعد قطاع الخدمات من أهم مؤشرات التحول الاقتصادي ويأتي لاحقاً بعد التحول نحو الصناعة، كما أن الصادرات الخدمية لها مساهمةً هامةً في الناتج المحلي في العديد من الدول وخاصةً في الدول النامية. يهدف البحث انطلاقا من ذلك إلى دراسة تأثير الصادرات الخدمية في الناتج المحلي الإجمالي في سورية، حيث يقوم البحث أولاً بدراسة واقع الصادرات السورية السلعية والخدمية وتركيب الصادرات الخدمية، و من ثم دراسة العلاقة بين الصادرات الخدمية وإجمالي الصادرات، والعلاقة بين الصادرات الخدمية والناتج المحلي الإجمالي. يخلص البحث إلى وجود تأثيرٍ إيجابي لكلٍ من الصادارت الخدمية في إجمالي الصادرات، والصادرات الخدمية في الناتج المحلي الإجمالي. وهي النتيجة التي تبين أهمية الصادرات الخدمية في سورية وخاصةً في المرحلة المستقبلية.